Economics (Sydney : McGraw-Hill, 1998)
An introduction to Australian capitalism. Macroeconomic activity: Output, employment and fiscal policy. Money, monetary policy and economic stability. Economic growth and development...
Keywords: Australia; Economics; Economics; Australia -- Economic conditions; Australia -- Economic policy; Australia -- Economic policy